Evaluation of initial and medium-term follow-up results of balloon aortic valvuloplasty in severe aortic valve stenosis in newborns, infants and children in Alexandria, Egypt - Adel, Hani Mahmoud (International Journal Of Community Medicine And Public Health, 2019)
Background: Aortic valve stenosis (AVS) represents 3%–7% of all congenital heart diseases. Balloon aortic valvuloplasty (BAoV) has been established as an alternative to surgery for therapy of AVS in infants and children; and has proven to be an effective method for decreasing the gradient between the left ventricle and the aorta. The objective of the study was to evaluate the initial and medium-term results of BAoV in newborns, infants and children with severe AS, treated at the Alexandria University Children’s Hospital. Methods: Thirty-seven newborns, infants and children with severe AS treated by B AoV between 2009 and 2017 were studied. They were followed-up for at least 1year post- ballooning by clinical and echocardiographic evaluation. Results: The mean AoV annulus diameter by echo was 13.1±4.4 mm and by angiographic measurement was 12.8±4.3 mm. The mean Doppler gradient across AoV was 91.8±14.7 mmHg, compared to mean catheter gradient of 66.1±13.4 mmHg. The mean inflated balloon diameter was 12.1±4.1 mm. The mean balloon/AoV annulus ratio by angiogram was 0.94±0.03 (0.88–1). The mean pressure gradient across the AoV post-ballooning was 21.5±6.9 mmHg by Doppler and was 10.3±4.7 mmHg by catheter, both were significantly less than pre-ballooning values (p<0.001). The procedure was successful in all the cases. Only one case died. Post -ballooning aortic incompetence was moderate in 2 cases (5.4%) and severe in only one case (2.7%). Conclusions: Balloon aortic valvuloplasty is an effective and safe technique for relieving severe aortic valvular stenosis with acceptable morbidity and minimal mortality, particularly with the new catheter and balloon technology.